The Bilingual Gullah Geechee: Diversity in African American Language - Berry, Jessica R. (Seminars in Speech and Language, 2025)
This article explores the linguistic and cultural significance of Gullah Geechee, an English-based Creole language, and its speakers as bilingual users. It examines the historical roots, linguistic features, and sociocultural importance of Gullah Geechee, which emerged from the interaction of African languages and English during the transatlantic slave trade. The study highlights Gullah Geechee's role as a linguistic variety used by African Americans, focusing on its phonological, syntactical, and lexical traits while challenging the marginalization of both Gullah Geechee and African American English as “broken” English. This article also looks at generational shifts in language use and identity among Gullah Geechee speakers, from historical stigmatization to a modern revival of cultural pride. It advocates for recognizing Gullah Geechee and African American English as legitimate languages, promoting culturally responsive teaching and bidialectal education. Emphasizing the need for systemic change, this article calls for the validation of heritage languages to support linguistic justice, academic success, and cultural preservation. Through its exploration of language structures, educational frameworks, and social attitudes, this work contributes to discussions on bilingualism and the preservation of marginalized dialects in American society.
Keywords: African American English; diversity; Gullah Geechee; generational shifts; linguistic features